Efficient computation of zeros of the moving average operator with real matricial coefficients - M. O. Salau (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
This paper proposes a computationally efficient procedure for evaluating the zeros of the vector moving average operator whose coefficients are matrices. A feature of the proposed method is that it is not necessary to explicitly construct the determinantal equation from a given moving average operator in order to evaluate its zeros. Application of the procedure is illustrated and numerical examples are provided to demonstrate the relative computational accuracy of the suggested method.
urn:nbn:de:kobv:11-10056993
Keywords: 330